2021
DOI: 10.2319/022321-147.1
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone changes after molar protraction in young adults with missing mandibular second premolars or first molars

Abstract: Objectives To assess the changes in alveolar bone of the mandibular second molars following molar protraction and investigate the factors associated with the alveolar bone changes. Materials and Methods Cone-beam computed tomography of 29 patients (mean age 22.0 ± 4.2 years) who had missing mandibular premolars or first molars and underwent molar protraction were reviewed. Alveolar bone level was measured as the distance from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…molars at pretreatment may have less alveolar bone resorption distal to the second molars following protraction [20]. The patient, in this case, had a medium horizontal angle of the #48 initial state, a high Nolla stage, a young age, and the presence of large eruption dynamics, so it had more chances to erupt spontaneously and move mesially following the protraction of the second molars.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…molars at pretreatment may have less alveolar bone resorption distal to the second molars following protraction [20]. The patient, in this case, had a medium horizontal angle of the #48 initial state, a high Nolla stage, a young age, and the presence of large eruption dynamics, so it had more chances to erupt spontaneously and move mesially following the protraction of the second molars.…”
Section: Discussionmentioning
confidence: 74%
“…It has been proved that the younger the age, the larger the third molar Nolla stage, and the closer the mandibular third molar is to the occlusal plane, the more it tends to move proximally to the neighboring teeth [ 19 ]. Studies also indicated that patients with impacted and mesially angulated third molars at pretreatment may have less alveolar bone resorption distal to the second molars following protraction [ 20 ]. The patient, in this case, had a medium horizontal angle of the #48 initial state, a high Nolla stage, a young age, and the presence of large eruption dynamics, so it had more chances to erupt spontaneously and move mesially following the protraction of the second molars.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with the anterior teeth, the posterior teeth are less susceptible to root resorption. 28 The treatment duration tends to be prolonged when molars are extracted, especially for individuals awaiting the eruption of the third molars. 22 This aspect is important and should be communicated to the patient at the start of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This technique improves the quality of outcomes, makes the treatment of complex cases possible and is especially useful in less compliant or non-compliant patients (Jung, 2011; Lee et al, 2018). Using mini-screws as TAD, mandibular molar protraction was an alternative to conventional prosthetic treatment for missing second premolars or first molars (Baik et al, 2022). Distal movements of the mandibular molars were able to be accomplished by traction between lower dentition and mini-screws inserted in the mandibular buccal shelf (MBS) (Park et al, 2005) or in the retro-molar area (Poletti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%